Three-dimensional numerical study of cooling water discharge of Daya Bay Nuclear Power Plant in southern coast of China during summer - Geng, Bingxu; Lu, Lingyan; Cao, Qian; Zhou, Wen; Li, Shiyu; Wen, Ding; Hong, Man (Frontiers in Marine Science, 2023)
The impact of thermal pollution caused by cooling water discharge of power plant on the surrounding marine ecology has been a hot issue in oceanographic research. To reveal the distribution pattern of cooling water discharge of Daya Bay Nuclear Power Plant in summer and the impact on the surrounding marine environment, this research established a high-resolution three-dimensional (3D) numerical model based on ECOMSED in the Daya Bay. The model results are consistent with the observations on the distribution of tide level and temperature. The simulated horizontal distribution of temperature rise is consistent with the distribution trend of remote sensing images. The study showed that the stratification of the Daya Bay water is stronger in summer. The cooling water mainly spreads in the surface layer, and the temperature rise in the bottom layer is not apparent. Quantitative analysis showed that around 18.8-21.6 km2 of the area has 1°C surface temperature rises. The area of temperature rises that exceeds 2 °C is between 6.2 and 8.1 km2. The area of temperature rises that exceeds 4 °C is between no more than 1.2 km2. The area with a bottom temperature rises of 1 °C does not exceed 2.2 km2, and there is no area that has a bottom temperature rise over 1 °C. The tidal dynamics process influences on the dispersion of cooling water discharge from Daya Bay Nuclear Power Plant, where the influence is more significant in the spring tide period than in the neap tide period. Our findings are consistent with previous researches.